Mechanisms behind grouting pressure jumping in low-permeability limestones and techniques for grouting pressure control - Zhenli FAN; Lutong CAO; Yong CUI; Zhiwei ZHANG; Fengda ZHANG (Meitian dizhi yu kantan)
BackgroundThe exploitation of the Carboniferous-Permian coalfields in China is gradually transitioning toward coal seams in lower formations. In this context, issues including the confined water hazards in the floor and karst water preservation become increasingly pronounced. During the advanced surface treatment of karst water hazards in coal seam floors, the unclear patterns of matching between grout selection and grouting pressure control lead to empirical parameter selection, thereby yielding poor performance of grouting reinforcement. MethodsThis study aims to deal with the phenomena of rapid pressure rise with a limited grout volume in the low-permeability argillaceous limestones within the top part of the Ordovician limestones in the Xin’an Coalfield, Western Henan. It investigated three typical grout types applied in surface treatment engineering of the Mengjin Coal Mine in the Xin’an Coalfield: pure cement grout, clay grout, and clay-cement grout through a range of experiments on the grouting pressure at the borehole head, static rheological characteristics, liquid-phase particle size distribution, zeta potential, electrical conductivity, microscopic morphology, and element distribution of the three grout types. Based on the flocculation mechanisms of cement and clay particles, this study analyzed pressure rise differences of three grout types from the physical and chemical perspectives. Results and ConclusionsPositively-charged cement particles and negatively-charged clay particles were prone to form three-dimensional reticular flocs due to strong electrostatic attraction. Consequently, the clay-cement grout exhibited large particles (sizes: > 600 µm). Furthermore, particles with sizes greater than 100 µm accounted for 78% of the total. These particles easily blocked up fractures. Compared to the cement grout, the clay-cement grout showed decreased electrical conductivity of 1.87 mS/cm. As a result, clay particles were observed to encapsulate cement particles post-mixing. The cement grout, characterized by small particle sizes, lower static yield stress, and low viscosity, can easily pass through narrow fractures, ensuring stable grouting pressure. In contrast, the clay-cement grout featured a static yield stress 4.5 times higher and a static viscosity 4.0 times compared to the cement grout. Therefore, such grout was prone to block fractures, and the pressure rise rate was approximately 10 times greater than that of the cement grout. An alternating grouting technique using clay-cement grout and cement grout was proposed following the principle of stepwise and gradual pressure rise, consisting of low-pressure filling, medium-pressure diffusion, and high-pressure fracture reinforcement (also referred to as the “three-stage” alternating grouting technique). This technique can significantly enhance the treatment efficiency, providing a valuable reference for grouting treatment of low-permeability limestones under similar conditions.